Blood cyst of the pulmonary valve causing right ventricular outflow tract obstruction: A case report. Issue 3 (16th October 2021) - Wang, Xiaoyan; Yang, Yanfeng; Zhang, Yong; Fan, Lingxia; Wang, Shushui
Abstract: Blood cysts are rare cardiac tumors, often involve the atrioventricular valves. Blood cysts are usually small and tend to be clinically silent. Here, we report a case of blood cyst adhered to the junction of the pulmonary valve and the right ventricular outflow, causing severe outflow obstruction. This case was initially misdiagnosed as pulmonary valve stenosis by transthoracic echocardiography (TTE) and even underwent percutaneous balloon pulmonary valvuloplasty (PBPV). As the right ventricle‐to‐pulmonary artery peak gradient did not decrease after PBPV procedure, the boy underwent TTE again and the diagnosis was corrected as blood cyst. The cystic mass was successfully resected subsequently, and the boy recovered well. Abstract : Echocardiographic views of blood cyst. (A) Parasternal short‐axis view of RVOT. Arrow indicates the blood cyst in the RVOT. (B) The blood flow accelerating in the RVOT, around the "ring cyst." (C) Subcostal short‐axis view of RVOT. Arrow indicates the blood cyst attaching to the pulmonary valve. PA, pulmonary artery; RA, right atrial; RPA, right pulmonary artery; RVOT, right ventricular outflow tract.